FBXW7 in gastrointestinal cancers: from molecular mechanisms to therapeutic prospects - Wang, Wanqing; Liu, Xue; Zhao, Lingling; Jiang, Kaipeng; Yu, Ziyi; Yang, Ruihan; Zhou, Wenshuo; Cui, Jiuwei; Liang, Tingting (Frontiers in Pharmacology, 2024)
F-box and WD repeat domain-containing 7 (FBXW7), formerly known as hCdc4, hAGO Fbw7, or SEL10, plays a specific recognition function in SCF-type E3 ubiquitin ligases. FBXW7 is a well-established cancer suppressor gene that specifically controls proteasomal degradation and destruction of many key oncogenic substrates. The FBXW7 gene is frequently abnormal in human malignancies especially in gastrointestinal cancers. Accumulating evidence reveals that mutations and deletions of FBXW7 are participating in the occurrence, progression and treatment resistance of human gastrointestinal cancers. Considering the current therapeutic challenges faced by gastrointestinal cancers, elucidating the biological function and molecular mechanism of FBXW7 can provide new perspectives and references for future personalized treatment strategies. In this review, we elucidate the key molecular mechanisms by which FBXW7 and its substrates are involved in gastrointestinal cancers. Furthermore, we discuss the consequences of FBXW7 loss or dysfunction in tumor progression and underscore its potential as a prognostic and therapeutic biomarker. Lastly, we propose potential therapeutic strategies targeting FBXW7 to guide the precision treatment of gastrointestinal cancers.